2020
DOI: 10.1101/2020.01.15.905331
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Carbon limitation leads to thermodynamic regulation of aerobic metabolism

Abstract: 13Organic matter (OM) metabolism in freshwater ecosystems is a critical source of uncertainty in 14 global biogeochemical cycles, yet aquatic OM cycling remains poorly understood. Here, we 15 present the first work to explicitly test OM thermodynamics as a key regulator of aerobic 16 respiration, challenging long-held beliefs that organic carbon and oxygen concentrations are the 17 primary determinants of respiration rates. We pair controlled microcosm experiments with 18 ultrahigh-resolution OM characterizati… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 49 publications
2
21
0
Order By: Relevance
“…This result challenges classical theories that use the concentrations of bulk substrate pools (such as organic carbon and oxygen) as the sole driving factors of aerobic respiration, notably excluding the influence of OM chemistry on biogeochemistry. The substrate-explicit model is built upon recent experimental studies that reveal a close relationship between OM thermodynamics and aerobic respiration (Graham et al, 2017;Graham et al, 2018;Garayburu-Caruso et al, 2020). Our test cases are broadly consistent with the conclusions of these studies, indicating a need to revise classic theory via incorporation of OM thermodynamics into our understanding and modeling of aerobic respiration.…”
Section: Dicussionsupporting
confidence: 73%
See 1 more Smart Citation
“…This result challenges classical theories that use the concentrations of bulk substrate pools (such as organic carbon and oxygen) as the sole driving factors of aerobic respiration, notably excluding the influence of OM chemistry on biogeochemistry. The substrate-explicit model is built upon recent experimental studies that reveal a close relationship between OM thermodynamics and aerobic respiration (Graham et al, 2017;Graham et al, 2018;Garayburu-Caruso et al, 2020). Our test cases are broadly consistent with the conclusions of these studies, indicating a need to revise classic theory via incorporation of OM thermodynamics into our understanding and modeling of aerobic respiration.…”
Section: Dicussionsupporting
confidence: 73%
“…For example, a present paradigm in environmental science views aerobic respiration rates as being primarily determined by kinetics (i.e., organic carbon (OC) and oxygen concentrations). However, recent field and laboratory studies suggest that OM thermodynamics can be a main driver of aerobic respiration (Graham et al, 2017;Graham et al, 2018;Stegen et al, 2018b;Garayburu-Caruso et al, 2020). Conventional lumped biogeochemical models are not completely effective for addressing this issue because the thermodynamic properties of substrates are a function of chemical composition of compounds constituting OM pools.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, data collected using an FTICR-MS will include information about any ionizable compound, not just those associated with biological systems 61 . Despite this potential limitation, previous studies have demonstrated that this type of data still contains biogeochemically relevant information 1,2,4,16,17 . Therefore, the three dendrograms described above can resolve the potential relationships between molecular formula based upon a point of view, which is agnostic to a molecular formula's source (MCD), a point of view which encompasses a putative biochemical point of view (TD), and an integrated view (TWCD).…”
Section: Resultsmentioning
confidence: 99%
“…nvironmental metabolomics enables the investigation of the metabolic processes and interactions occurring within an ecosystem and can provide deep insight into ongoing biogeochemical cycles [1][2][3][4] . High-resolution mass spectrometric techniques, like Orbitrap-MS, Fourier transform ion cyclotron resonance MS (FTICR-MS), and ion mobility spectrometry MS (IMS-MS), among others have allowed researchers to investigate the individual carbon compounds that constitute natural organic matter (NOM) 1,[5][6][7] .…”
mentioning
confidence: 99%
See 1 more Smart Citation